Direct Laser Patterning of CdTe QDs and Their Optical Properties Control through Laser Parameters - Francesco Antolini (Nanomaterials, 2022)
Direct laser patterning is a potential and powerful technique to localize nanomaterials within a host matrix. The main goal of this study is to demonstrate that by tuning some parameters of a laser source, like power and laser pulse frequency, it is possible to modify and tune the optical properties of the generated quantum dots (QDs) within a host matrix of a specific chemical composition. The study is realized by using cadmium telluride (CdTe) QD precursors, embedded in polymethylmethacrylate (PMMA) host matrix, as starting materials. The patterning of the CdTe QDs is carried out by using a UV nanosecond laser source at 355. Fluorescence microscopy and photoluminescence spectroscopy, associated with transmission electron microscopy, indicate that it is possible to obtain desired patterns of QDs emitting from green to red of the visible spectrum, due to the formed CdTe QDs. Preliminary highlights of the CdTe QDs’ formation mechanism are given in terms of laser power and laser pulse frequency (repetition rate).